Poverty and employment in Latin America: 1990-2005 - Simone Cecchini; Andras Uthoff (CEPAL Review, 2008)
What factors led to the reduction of poverty in Latin America from 1990 onwards? This article looks into the key factors that have played a part in reducing poverty in the region, including, in particular, employment and remuneration for work. With data from household surveys, the authors discuss the ways in which changes in the working age population, in its participation in economic activity, in employment rates and in income from work and other sources affect the per capita incomes of families in the lowest deciles of income distribution and hence in poverty indicators.